6(z-2)+5z-2=

Simple and best practice solution for 6(z-2)+5z-2= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(z-2)+5z-2= equation:


Simplifying
6(z + -2) + 5z + -2 = 0

Reorder the terms:
6(-2 + z) + 5z + -2 = 0
(-2 * 6 + z * 6) + 5z + -2 = 0
(-12 + 6z) + 5z + -2 = 0

Reorder the terms:
-12 + -2 + 6z + 5z = 0

Combine like terms: -12 + -2 = -14
-14 + 6z + 5z = 0

Combine like terms: 6z + 5z = 11z
-14 + 11z = 0

Solving
-14 + 11z = 0

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '14' to each side of the equation.
-14 + 14 + 11z = 0 + 14

Combine like terms: -14 + 14 = 0
0 + 11z = 0 + 14
11z = 0 + 14

Combine like terms: 0 + 14 = 14
11z = 14

Divide each side by '11'.
z = 1.272727273

Simplifying
z = 1.272727273

See similar equations:

| 5(x+4)=-2x-8 | | 8y+3(y-5)=6(y+1)-2 | | 3(c-5)+5=2+c-12 | | 3(1-10x)= | | -8(2-7p)=-16-8p | | 90-9x=-70-x | | 6v-32=2(v-8) | | x+x-3002=7878 | | x-2+9k+3= | | (Y+8)(y+3)=0 | | X^4-3x^2-6=0 | | 145=216-u | | 8-3h-6= | | 3m+1-m=-7+m-1+1 | | -10k=250 | | -3x-18=7(x+6) | | -8k+9k= | | 85=7x-5(4x-4) | | y=16x+260 | | -3x+12=-3(2x+2) | | -5x+7(x-3)=8x-9 | | 2x+-7=66 | | -7(3x-4)+7=-21x+35 | | -47=x-67 | | 3+6x=54 | | -x^2-9n-18=0 | | -3x+12=-3(2y+2) | | -14x-8=-7x-12 | | 7x+5(-2x+3)=-3 | | -2(5p-1)-5p=-40-8p | | -4(x-2)=x+-7 | | 10+-1z=0 |

Equations solver categories